Low‐Temperature Fast Production of Carbon and Acetic Acid Dual‐Promoted Pd/C Catalysts. Issue 60 (10th October 2019) - Yao, Xiuchao; Ni, Lin; Yu, Chang; Zhang, Mengdi; Wei, Qianbing; Huang, Huawei; Guo, Wei; Huang, Hongling; Chang, Jiangwei; Qiu, Jieshan
Abstract: The Pd/C catalysts are widely used in synthesis of fine chemicals in industry, but their production suffers from a complicated two‐step process involving impregnation and reduction, and requires large amounts of solvents and reductant, which would lead to a series of issues such as time consumption, resource waste and environmental pollution. Herein, ultra‐small Pd nanoparticles uniformly anchored on carbon nanotubes (Pd/CNTs) were synthesized by using a one‐pot and low‐temperature reduction strategy. The present process/technology is very sensitive to and controlled by the supports and solvents, and the carbon support and acetic acid synergistically play crucial and decisive roles in the fast production of Pd/C catalysts. Also, the used solvents can be recycled and reutilized, which meets the requirements of sustainable chemistry and green economy. When the as‐obtained Pd/CNTs catalyst was used to catalyze the oxidation of benzyl alcohol to benzaldehyde, it achieved a conversion efficiency as high as 99.3 % and a high selectivity up to >99.9 %. The simple, scalable and environmentally friendly strategy can be extended to anchor Pd nanoparticles on various carbon substrates, which sheds a new light on the synthesis of Pd/C catalysts. Abstract : Hitting the mark : Low‐temperature fast production of Pd/C catalysts is presented by a carbon and acetic acid dual‐promoted strategy, indicative of solvent‐ and support‐responsive and sensitive behavior. The used acetic acid can be recovered and reutilized. The simple, potentially scalable, and green strategy could also be extended to other carbon materials.